Morphological characteristics and ecological significance of Volga‐Caspian Basin fish tumors - V. V. Volodina; M. P. Grushko; N. N. Fedorova; E. A. Voronina; N. Yu. Terpugova; M. A. Gulyaeva (Юг России: экология, развитие, 2020)
Aim. To investigate the histological structure of fish tumors in the Volga Delta and the northern part of the Caspian Sea to assess the habitat quality of aquatic organisms.Material and Methods. Neoplasms identified in the following representatives of ichthyofauna were analyzed: black‐backed herring, roach, asp, perch, carp, pike, zander, catfish and bream. Biological material was collected during specialized scientific research expeditions to the Volga Delta in April‐October 2015‐2018. Sample analysis were carried out in accordance with standard histological techniques.Results. The research shows that tumors were localized both on the surface of the body and in the internal organs of fish. During the period of investigation individuals examined were diagnosed with the following cancers: adenomectomy, basal cell carcinoma, hepatocellular carcinoma, polypous cancer, rhabdomyoma, fibrosarcoma and follicular, epidermal papilloma. The most common pathology in the populations of semi‐migratory, migratory and river fish was a malignant tumor, fibrosarcoma, registered in six of the ten examined ichthyofauna species. Epithelial papilloma was most often observed in catfish. There were no oncological diseases were detected in rudd.Conclusions. Histological analysis of tumors recorded in the Volga ichthyofauna has shown that a number of identified disorders are irreversible and will inevitably lead to the reduction of fish resources as well as generally indicating the environmental problems of the habitat of aquatic organisms.